(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
In this research, the oscillation and the asymptotic behavior of a half-linear three-dimensional neutral differential system of the second order have been studied, where all the non-oscillating solutions have been classified into 16 different classes, and then sufficient conditions were given to prove that most of these classes are inactive and non-occurring, that is empty, as for the rest classes, it has been proven that all its bounded solutions, either oscillating or non-oscillating, converge to zero when , and all unbounded solutions, are either oscillating or non-oscillating, goes to as . Some examples are given to illustrate the obtained results